Coronary microvascular dysfunction: A review of recent progress and clinical implications - Rehan, Rajan; Yong, Andy; Ng, Martin; Weaver, James; Puranik, Rajesh (Frontiers in Cardiovascular Medicine, 2023)
The coronary microcirculation plays a cardinal role in regulating coronary blood flow to meet the changing metabolic demands of the myocardium. Coronary microvascular dysfunction (CMD) refers to structural and functional remodelling of the coronary microcirculation. CMD plays a role in the pathogenesis of obstructive and non-obstructive coronary syndromes as well as myocardial diseases, including heart failure with preserved ejection fraction (HFpEF). Despite recent diagnostic advancements, CMD is often under-appreciated in clinical practice and may allow for the development of novel therapeutic targets. This review explores the diagnosis and pathogenic role of CMD across a range of cardiovascular diseases, its prognostic significance, and the current therapeutic landscape.